PENERAPAN MODEL QUANTUM TEACHING BERBASIS ANDRAGOGI UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR WARGA BELAJAR KEJAR PAKET C DI PKBM MANDIRI KABUPATEN SIDOARJO - Ratna Mufidah; YATIM RIYANTO; I KETUT ATMAJA (JPUS: Jurnal Pendidikan Untuk Semua, 2018)
Abstract: Motivation and learning outcomes WB class X Package C English subject matter Descriptive Text in PKBM Mandiri is still low. This happens because the tutor is less innovative in applying the learning model so that in the delivery of the subject matter, the tutor still dominates (teacher centered), resulting in the passive WB. Therefore, it is necessary to apply the model of Quantum Teaching based on Andragogy. The purpose of this study is to describe the application of the model of Quantum Teaching based on Andragogy as well as the motivation and learning outcomes of WB after applying the learning model.The research is a Classroom Action Research (PTK). The implementation of this classroom action research is conducted through two cycles in which each cycle consists of four stages: (1) planning, (2) action implementation, (3) observation, and (4) reflection. Subject in this research is WB class X Paket C PKBM Mandiri Sidoarjo. Data collection techniques are done at the end of the cycle using tests, observations, and documentation. The success indicator of this class action research is WB motivation in learning activity of at least 75%, WB learning outcomes that get the value according to KKM (â‰¥75) at least 75%. While the results of this study certainly can be useful for WB, tutors, and institutions.The results obtained from the motivation and learning outcomes in cycle I are: (1) average class 73.40%; (2) mastery learning 36,60 %%; (3) average learning outcomes 70.83%; Learning motivation in cycle II are: (1) class average 79,93%; (2) learn 90% mastery; (3) average learning outcomes WB 76%;Based on the research results can be concluded that with the application of learning model Quantum Teaching Based Andragogy can improve motivation and learning outcomes WB in learning English material Descriptive Text in PKBM Mandiri Sidoarjo district.